ANALISIS SISTEM INFORMASI KEUANGAN REGIONAL DALAM MENINGKATKAN KUALITAS INFORMASI UNTUK UNIT KERJA DAERAH BANDUNG - Nurul Amalia Ramdan (Jurnal Apresiasi Ekonomi, 2020)
This results are aimed at determining (1) the implementation of Region Finance Information System (SIKD), (2) the information quality (3) the influence degree of the implementation of the Region Finance Information System (SIKD) on the information quality for Regional Work Unit of Bandung. Results method used is a descriptive method. The data collection technique conveyed is a survey method. Data of the application region finance information system in increasing the information quality is a data primer which derives from questionnaires distributed to 23 respondents by involving the Agency and the Department of Bandung.The results data showed that the implementation of Region Finance Information System (SIKD) in Regional Work Unit of Bandung has been running well, included in the high rate category. Meanwhile, the information quality on Regional Work Unit of Bandung, included in the middle rate category. The implementation of Region Finance Information System (SIKD) has a positive impact for the information quality in Regional Work Unit of Bandung by 38,81% and the balance of 61,19% influenced by other factors not examined in this results.